2004
DOI: 10.3732/ajb.91.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and anatomy of Lycopersicon esculentum fruit peels and enzyme‐treated samples

Abstract: We report the biomechanics and anatomy of fruit wall peels (before and after cellulase/pectinase treatment) from two Lycopersicon esculentum cultivars (i.e., Inbred 10 and Sweet 100 cherry tomatoes). Samples were tested before and after enzyme treatment in uniaxial tension to determine their rate of creep, plastic and instantaneous elastic strains, breaking stress (strength), and work of fracture. The fruit peels of both cultivars exhibited pronounced viscoelastic and strain-hardening behavior, but differed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 22 publications
6
52
0
1
Order By: Relevance
“…AC and DFD fruits have similar cuticle anatomies (Fig. 7, A-D), with substantial epidermal cell encasement, where several outer epidermal cell layers show cuticularization of the anticlinal and periclinal cell walls, as has been described in several tomato cultivars (Bargel and Neinhuis, 2004;Matas et al, 2004). Fruits of both cultivars also showed similar patterns of cellulosic cell wall ramification within the cuticular layer, as revealed by staining with toluidine blue (Fig.…”
Section: Microscopic Analysis Of Cuticlessupporting
confidence: 66%
See 2 more Smart Citations
“…AC and DFD fruits have similar cuticle anatomies (Fig. 7, A-D), with substantial epidermal cell encasement, where several outer epidermal cell layers show cuticularization of the anticlinal and periclinal cell walls, as has been described in several tomato cultivars (Bargel and Neinhuis, 2004;Matas et al, 2004). Fruits of both cultivars also showed similar patterns of cellulosic cell wall ramification within the cuticular layer, as revealed by staining with toluidine blue (Fig.…”
Section: Microscopic Analysis Of Cuticlessupporting
confidence: 66%
“…The cuticle itself is also thought to have an important influence on the biomechanical properties of ripening fruit (Petracek and Bukovac, 1995;Bargel and Neinhuis, 2004;Matas et al, 2004;Bargel and Neinhuis, 2005;Edelmann et al, 2005) and studies with isolated tomato fruit cuticles suggest that their relative contribution to tissue strength increases markedly during ripening, an idea that was previously suggested by analyses of intact tomato fruits (Jackman and Stanley, 1994). Taken together, a growing body of evidence suggests that, as with cell wall metabolism, dynamic changes in the structure and composition of the fruit cuticle that lead to a reduction in fruit firmness are likely to be an integral and regulated part of ripening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was found that cellulose fibres are mainly randomly oriented in cuticles of mature and ripe tomato fruits and Agave Americana young leaves [9,10], the position and distinction between groups of polysaccharides cannot be ascertained by such analytical techniques. On the other hand, stains like osmium tetroxideuranyl acetate-lead citrate combination [12], calcofluor white [9], ruthenium red [13], periodic acid-thiosemicarbazide-silver proteinate tests [12,14] or chlor-zinc-iodine [15] have been used for detecting polysaccharides in cross-sections of isolated leaf and fruit cuticles by electron, optical and fluorescence microscopy. Nevertheless, the lack of specificity of the dyes, the potential degree of impregnation of polysaccharides with chiefly lipidic cuticular components, and the restrictions to observe stained tissues at higher magnifications by optical and fluorescence microscopy, pose an obstacle for elucidating the nature and location of polysaccharides in the cuticle.…”
Section: Introductionmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum) fruit also serve as a powerful system for investigating the physical properties and biosynthesis of the cuticle fostered in large part by the abundance of cuticular lipid deposited during fleshy fruit development, its astomatous nature, and relevance in fruit cracking and postharvest storage Scott, 1997, 1998;Matas et al, 2004;Bargel and Neinhuis, 2005). Genomics-and proteomics-based approaches have identified genes and proteins preferentially expressed in the fruit peel, and perturbation of several genes through mutagenesis has revealed altered fruit cuticle phenotypes (Vogg et al, 2004;Hovav et al, 2007;Mintz-Oron et al, 2008;Isaacson et al, 2009;Yeats et al, 2010;Matas et al, 2011).…”
mentioning
confidence: 99%